Analisis Tingkat Pemahaman Siswa SMA 5 Tegal Tentang Pentingnya Pemeriksaan Payudara Sendiri (Sadari) - Meyliya Qudriani; Seventina Nurul Hidayah; Riska Arsita Harnawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Breast self-examination (BSE) is learning to see and examine your own breasts every month (Rasjidi, 2021). The main goal of BSE is to find breast cancer at an early stage so that treatment can be better. Lack of understanding or lack of information about breast cancer and steps to prevent early detection causes many women to be less or less interested in having this examination. Breast cancer is the cancer with the second highest prevalence after cervical cancer in Central Java in 2021, namely cervical cancer at 1.2% or the equivalent of 19,734 people and breast cancer at 0.7% or the equivalent of 11,511 people. Based on the preliminary study conducted, the results showed that of the 10 questions about BSE at SMA 5 Tegal, 6 out of 10 respondents answered that they did not know or had a low understanding of BSE, while the other 4 respondents indicated sufficient understanding about BSE. The aim of this study was to evaluate SMA 5 Tegal students' understanding of the importance of breast self-examination (BSE) in early detection of breast cancer. The research method that will be used in this research is a quantitative approach with a cross sectional design. The population of this research was 117 female students of SMA 5 Tegal class XI (adolescent girls), with sampling using the total sample. The results of this research show that the majority of respondents have a good understanding of BSE, namely 89 respondents (76.1%), where this respondent's understanding is obtained from good knowledge about BSE, knowing the correct BSE examination techniques.